Mobile Ticketing Menggunakan Teknologi Near Field Communication pada Bus Rapid Transit Bandar Lampung: Studi Pendahuluan - Wicaksono, Dwi Satrio; Ulvan, Ardian; Ulvan, Melvi (JITROKOM, 2015)
Abstract â Trip fare payment using paper money on public transport Bus Rapid Transit Bandar Lampung considered normal. The payment process can be improved using a technology called Near Field Communication (NFC) in android smartphone, which in turn was named after the mobile ticketing process. The author tries to analyze this technology using SWOT analysis (Strength, Weaknesses, Opportunities, Threats) before the technology is applied. The results obtained are in this technology: Strenghts - efficient use, Weaknesses - all those not yet ready to use, Opportunities - the organizers can reap the benefits of the application of this technology, Threats - security is still doubted by consumers. Solution of existing problems that the government should start first by issuing government regulations and the ecosystems that support for NFC technology.Â Keywords - SWOT Analysis, Mobile Ticketing, Near Field Communication (NFC).Â Intisari â Pembayaran tarif perjalanan menggunakan uang kertas pada transportasi publik Bus Rapid Transit Bandar Lampung dianggap sudah biasa. Proses pembayaran dapat ditingkatkan menggunakan teknologi Near Field Communication (NFC) pada smartphone android, yang selanjutnya proses ini dinamakan mobile ticketing. Penulis mencoba menganalisa teknologi ini menggunakan metode analisa SWOT (Strenght, Weaknesses, Opportunities, Threats) sebelum teknologi ini diterapkan. Hasil yang didapatkan yaitu teknologi ini memiliki: Strenghts â efisien penggunaannya, Weaknesses â semua pihak belum siap penggunaannya, Opportunities â pihak penyelenggara dapat meraup keuntungan dari pengaplikasian teknologi ini, ThreatsÂ â keamanan masih diragukan oleh konsumen. Solusi dari permasalahan yang ada yaitu pemerintah harus memulai terlebih dahulu dengan mengeluarkan peraturan pemerintah dan ekosistem yang mendukung untuk teknologi NFC.Kata kunciÂ â Analisa SWOT, Mobile Ticketing, Near Field Communication (NFC).